2004
DOI: 10.1095/biolreprod.103.021170
|View full text |Cite
|
Sign up to set email alerts
|

Tsga10 Encodes a 65-Kilodalton Protein That Is Processed to the 27-Kilodalton Fibrous Sheath Protein1

Abstract: We had previously reported the isolation of the testis-specific human gene Tsga10, which is not expressed in testes from two infertile patients. To study its role and function, we cloned the mouse homologue Mtsga10. Mtsga10 localizes to mouse chromosome 1, band B. This region is syntenic with human chromosome 2q11.2, where Tsga10 is located. We demonstrate that Mtsga10 mRNA is expressed in testis, but not in other adult tissues, and in several human fetal tissues and primary tumors. We uncovered that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 36 publications
(49 reference statements)
1
45
0
Order By: Relevance
“…The gene is located on chromosome 2q11.2 and consists of 19 exons extending over 3 kb. TSGA10 is expressed during spermatogenesis and codes for a protein found in the fibrous sheath, a major sperm tail structure in mature spermatozoa in the mouse (19). In this study, we showed that the testis-specific gene TSGA10 is over-expressed in some types of malignancies and induces an IgG response in patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The gene is located on chromosome 2q11.2 and consists of 19 exons extending over 3 kb. TSGA10 is expressed during spermatogenesis and codes for a protein found in the fibrous sheath, a major sperm tail structure in mature spermatozoa in the mouse (19). In this study, we showed that the testis-specific gene TSGA10 is over-expressed in some types of malignancies and induces an IgG response in patients.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, we investigated TSGA10 mRNA expression in normal tissues and tumors. TSGA10 was originally identified by differential mRNA display as a testis-specific gene (18,19). Quantitative real-time RT-PCR analysis showed over-expres- …”
mentioning
confidence: 99%
“…These controls have previously been employed in the successful optimisation of other cell-based assays used for this purpose. Firstly, transfection efficiency was checked using the well validated method of GFP transfection to produce auto-fluorescent cells (Modarressi et al 2004). This confirmed our method of transfection was robust.…”
Section: Study Limitationsmentioning
confidence: 55%
“…Mouse mHIF-1aI.1 and human hHIF1aTe are expressed in the postacrosomal region and the midpiece of spermatozoa [16,17]. Here, we demonstrate that HIF-1a interacts with the filament-building sperm protein TSGA10 [18], which modulates the intracellular localization of HIF-1a. Since TSGA10 expression was recently demonstrated also in embryonic tissue, different adult organs like brain, kidney and heart as well as malignant tissues, this finding may have also implications for tissue-dependent regulation of HIF-1 activity [19].…”
Section: Introductionmentioning
confidence: 67%
“…Fulllength TSGA10 (Accession No. AF530050) was amplified by PCR from pEGFP2mTSGA10 [18]. Fragments of TSGA10 corresponding to the indicated amino acids were amplified by PCR from the fulllength entry vector.…”
Section: Plasmid Constructionsmentioning
confidence: 99%